Interpretasi Biomarker dan Korelasi Minyak-Batuan Induk pada Sumur TNG-1, Cekungan Sumatra Tengah - Putri Dwi Afifah; Muhammad Agni Gustama; Sri Desdita Komari; Lusitania; Aisyah Minzikrina Masbar Rus; Widi Atmoko (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study interprets biomarker characteristics and evaluates the genetic relationship between oil samples and potential source rocks from the TNG-1 well in the Cekungan Sumatra Tengah. The analysis was conducted using oil and rock geochemical parameters, n-alkane chromatograms, terpene and sterane distributions, as well as sterane ternary plots (C₂₇–C₂₈–C₂₉). The results indicate that oil samples at intervals of 5238–5277 ft, 5246–5248 ft, and 5266–5268 ft exhibit consistent geochemical characteristics and suggest thermal maturity within the early to mid-mature oil window. In contrast, rock samples at intervals of 4814 ft, 5046 ft, and 5151 ft show immature characteristics, indicated by CPI > 1.0, high Pr/nC₁₇ ratios, and n-alkane distributions biased toward long-chain compounds. Biomarker analysis reveals similarities in n-alkane distribution patterns, isoprenoid ratios, and C₂₇–C₂₈–C₂₉ sterane compositions between oil and source rock samples, indicating a strong genetic relationship. Sterane compositional correlation suggests that most samples, both oil and rock, originated from shallow lacustrine to estuarine depositional environments with significant higher-plant input. Overall, the oil samples show a strong correlation with the source rock at the 5151 ft interval based on the consistency of n-alkane, hopane, and sterane patterns.